AKTIVASI LITIUM SEBAGAI KATALISATOR PADA REAKSI PEMBENTUKAN HTPB - Wibowo, Heri Budi; Rosita, Geni (Indonesian Journal of Aerospace, 2004)
HTPB usually used as propellant fuel binder. This paper studied anionic polymerization of butadiene to form HTPB (Hydroxy Terminated Polybutadiene) with litium as catalyst. In practice, litium must be reactivated to remove antioxidant that surround it. Butadiene is polymerized in a 250 mL autoklave at room temperature and free oxygen. Litium was reactivated by melting and deforming. The polymer form was terminated by ethylene oxide to form HTPB. After it was washed by benzene and aquadest, HTPB structure was analyzed with FTIR at 910 cm and 970 cm. Investigation of the polymerization could produced HTPB if litium as catalyst was reactivated. HTPB resulted contain maximum 30 percent structure cis-1,4 HTPB. The average molecule weight can be control very well based on amount of litium (catalyst).